Does perceived stress mediate the relationship between financial status, depression, and anxiety in caregivers at risk for cardiovascular disease (CVD)?. (11th May 2022) - Smith, J; Mcneely, C; Chung, ML; Miller, JL; Biddle, M; Schuman, DL; Rayens, MK; Lennie, TA; Hammash, M; Mudd-Martin, G; Moser, DK
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): National Institutes of Health National Institute of Nursing Research Background/Introduction: Caregivers are at high risk of anxiety and depression, and caregiver mental health is linked to higher CVD risk in caregivers over their non-caregiving peers. Most research focuses on caregiver burden as a primary cause for caregiver's emotional distress, such as anxiety and depression. Other stressors like financial burden are less emphasized, despite widespread documentation of financial burden as a key social determinant of health. We hypothesize financial status predicts anxiety and depression through perceived stress. Purpose: To identify the relationship between financial status and caregiver anxiety and depression and determine if it is mediated by perceived stress. Methods: We analyzed cross-sectional data from the Rural Intervention for Caregiver's Heart Health study. Anxiety was assessed using the Brief Symptom Inventory – Anxiety subscale (range 0 -3.5) and depression was assessed by the Patient Health Questionnaire –9 (range 0 - 27). Financial status was measured with one item that asked participants to rank their financial situation by level of comfort (not enough to make ends meet, enough to make ends meet, and comfortable), and perceived stress measured with Cohen's Perceived Stress Scale – 4. Analysis was performed separately for the two mental health outcomes using OLS regression and, to test mediation, the PROCESS macro for SPSS and the bootstrapping procedure with 5, 000 samples. We included age, gender, marital status, number of people in the household, body mass index, smoking status, and caregiver burden as covariates. Results: Of the 287 participants, average age was 54 ± 13; 76% were female, 95.8% were Caucasian, and 70.4% were married. Controlling for covariates, caregivers with not enough to make ends meet reported substantially greater depressive symptoms (b=2.22, 95% CI = 0.48 – 3.96) and marginally greater anxiety (b=0.23, 95% CI = -0.02 – 0.47) compared to caregivers who were financially comfortable. These associations were not mediated by perceived stress as hypothesized. Conclusions: Among caregivers who are at risk for CVD, financial status was important in reporting both depression and to a lesser extent, anxiety however perceived stress does not mediate this relationship. This is interesting as perceived stress is often a target for interventions that focus on reducing depression and anxiety in this population however our analysis emphasizes the importance of financial status alone. When designing interventions to reduce the CVD risk factors of anxiety and depression, more attention should be paid to relieving financial burden.